Theoretical understanding between competitiveness and productivity: firm level (2018)
(Eng) The objective of this article is to contribute to the understanding of the concept of competitiveness at firm level and its relation to productivity. To support the objective of this work, a systematic review of the literature was conducted and was subsequently structured an analysis of the elements found in the literature through systems thinking. Systems thinking enables to identify the cause and effect between the elements of competitiveness, highlighting the convergence and divergence between these elements. It was concluded that productivity stood out among the other elements confirming its importance in determining firm competitiveness. Limitations of this study consists on the theoretical nature, there is the need for an empirical study to verify the practical effect of productivity on competitiveness at the firm level.